SOCIO-ECONOMIC ASSESSMENT OF DIRECT SALES IN SICILIAN FARMS - Filippo Sgroi (Chiriotti Editori, 2015)
Many farmers today adopt direct sales as an entrepreneurial strategy in order to achieve a competitive advantage. The aim of this study has been to analyze the role that direct sales play in Sicilian farms and how the short food supply chain is able to valorize the endogenous resources of rural areas and increase the net income of farmer. Our results showed that direct sales, in conjunction with conventional sales, can represent a growing opportunity for farmers and lead to an improvement in the economic performances of agricultural businesses, an increase in farm investments and the creation of new job opportunities.